The customer awareness towards marketing campaign of Denai Alam Residentials in Shah Alam / Rahah Kamarudin - Kamarudin, Rahah (Faculty of Business and Management, 2006)
The purpose of study is to identify the awareness of customers towards marketing campaign of Denai Alam residential done by Guthrie Properties Development Holding Berhad (GPDH). It also will help the company to determine whether their marketing campaign had been done effectively or not. Based on the company, the customers' awareness towards marketing campaign can be gain by choosing the right tools, the frequency of doing campaign and the creativity of the campaign. if the level of awareness is high, it shows that the marketing campaign is done effectively and people know about the Denai Alam project as well. If not, GPDH need to come out with new strategy for their marketing campaign.